The stationary Stokes flow through a spherical region with large variations of density and viscosity coefficient - Płochocki, Z.; Kaźmierczak, B.; Peradzyński, Z. (Archives of Mechanics, 1996)
We are interested in flows of a fluid whose density changes abruptly after entering a certain region in R3. Flows of this kind may be useful in modelling such phenomena as propagating flames. Assuming that the region is a ball we find a closed-form solution for the flow homogeneous at infinity in the Stokes approximation. It is compared with the analytical solution in the Euler approximation. Such solutions can also be used as a test for numerical algorithms solving the flow equations.